Exploring patient satisfaction with interdisciplinary care of complex feeding problems - Claire Miller; Scott Pentiuk (The Beryl Institute, 2016)
Measures of patient satisfaction with health care experiences are recognized as essential in the healthcare market environment. To our knowledge, there are no specific patient experience measures that assess patient and caregiver satisfaction with a multidisciplinary approach to management of complex feeding and swallowing issues in pediatric patients. In order to explore patient experience and to identify opportunities for improvement, a pilot patient satisfaction survey was developed in an interdisciplinary feeding team clinic. Patients and families were surveyed following clinic encounters between July of 2014 and January of 2015. Likert style questions were used to assess experience with ease of scheduling, perception of the team's ability to understand feeding concerns, and to identify agreement with the appropriateness of recommendations. Two open-ended questions were used to elicit qualitative responses regarding what was positive about the experience and what could be improved or done differently. Qualitative responses were categorized by opportunities for improvement and affirmative statements. Analysis of survey results indicated high levels of satisfaction (96%) with the team's ability to understand feeding concerns and to provide feasible recommendations for treatment options. Satisfaction scores for scheduling were lower (92%); dissatisfaction with the next available options for appointments and with the overall length of the visit was identified. The pilot patient satisfaction project confirmed satisfaction with a multidisciplinary approach to feeding problems in pediatric patients, and identified opportunities for future quality improvement. Ongoing patient satisfaction measures will provide a mechanism to identify the effects of future improvement measures.